Evaluating William Gumede's elements of democratic deficit as an adverse feature of liberation movements in government : the case of the African National Congress (ANC) in South Africa - Henwood, Roland (University of Pretoria, 2024)
Dissertation (MA (Political Science))--University of Pretoria, 2024.